Determinan kejadian stunting di Puskesmas Alue Bilie Kabupaten Nagan Raya - Siti Zaidar Lubis (Jurnal SAGO Gizi dan Kesehatan, 2021)
Background: Stunting is condition a child's nutritional status that is not ideal which can Stunting is state of nutritional status children who are not ideal that can inhibit growth and development. Stunting events are influenced by various factors, namely birth length, exclusive breastfeeding history, family income, maternal education, maternal height nutrition knowledge, parity and parenting.Objective: Purpose this study is find the determinant stunting events in Alue Bilie Health Center of Nagan Raya Regency of Aceh Province.Method: The research design used is an observational comparative study with a case control approach. The population of this research is all mothers who have toddlers in Kuta Trieng Village. The number of samples is that all mothers have stunting toddlers as many as 42 people and toddlers who do not suffer from stunting as many as 42 people. Data was collected by interview using a questionnaire and anthropometric measurements of TB and age. Height using microtoise. Stunting was processed based on PMK no 2 of 2020. The data were analyzed using the Chi-Square test and Multiple Logistics Regression at a significance level of 95%.Results: Based on the results of the study found that there a relationship of exclusive breast milk history with stunting (ρ= 0.000), there a relationship of maternal nutritional knowledge with stunting (ρ= 0.000), there a income relationship with stunting (ρ= 0.024), there a relationship of maternal education with stunting (ρ= 0.034), exist parity relationship with stunting (ρ= 0.000), there a relationship of maternal height with stunting (ρ= 0.000) and there a parenting relationship with stunting (ρ= 0.003). Determinant factors that most affected stunting incidence were maternal height with an OR score of 24.8Conclusion: Factors that have a relationship with the incidence of stunting in toddlers in the work area of the Alue Bilie Health Center, Nagan Raya Regency, Aceh Province, namely the mother's education level, parity, exclusive breastfeeding, mother's level of knowledge, family income, mother's height and parenting patterns. The main determinant factors are parity, knowledge and maternal height.